Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1591769
|View full text |Cite
|
Sign up to set email alerts
|

Power Dependence of the RF Surface Resistance of MgB>inf<2>/inf<Superconductor

Abstract: Magnesium diboride (MgB 2 ) is a superconducting material that has a transition temperature (T c ) of ~40 K, which is ~30 K higher than niobium (Nb) that has been used for most superconducting RF cavities in the past decades. Last year, it was demonstrated that the RF surface resistance of MgB 2 can be lower than Nb at 4 K.One of the problems with other high-T c materials such as YBCO was its rapid increase in RF surface resistance with higher surface magnetic fields. Recently, we have shown that MgB 2 shows l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Due to the lower R s value of the MgB 2 material, the maximum value of the peak magnetic field achieved at the maximum power level is about 100 Oe, and the slight variation of R s starts at H mw ≈ 12 Oe (corresponding to P in = 20 dBm). The maximum peak magnetic field we achieved with the homogeneous cavity is smaller but of the same order of magnitude than those achieved in previous investigations in MgB 2 bulk and films [39], [40]; even in our MgB 2 material, the mw surface resistance weakly depends on the mw field, as already highlighted in [39] and [40].…”
Section: B Results As a Function Of The Input Powersupporting
confidence: 77%
“…Due to the lower R s value of the MgB 2 material, the maximum value of the peak magnetic field achieved at the maximum power level is about 100 Oe, and the slight variation of R s starts at H mw ≈ 12 Oe (corresponding to P in = 20 dBm). The maximum peak magnetic field we achieved with the homogeneous cavity is smaller but of the same order of magnitude than those achieved in previous investigations in MgB 2 bulk and films [39], [40]; even in our MgB 2 material, the mw surface resistance weakly depends on the mw field, as already highlighted in [39] and [40].…”
Section: B Results As a Function Of The Input Powersupporting
confidence: 77%
“…In [13], we proposed to use PLD to coat a cavity. To check the feasibility of this technique, we coated some substrates made of Nb and .…”
Section: Coating Techniquesmentioning
confidence: 99%
“…The surface finish does not look as good as that coated on sapphire because the Nb substrates had a very rough surface of 400 nm in rms roughness. This could have contributed to the higher surface resistance compared to the samples coated on smooth sapphire substrates [12], [13]. It was found that, although the surface resistance at low field is similar for both films with PLD and reactive evaporation techniques, the power dependence is very different.…”
Section: Power Dependence Of Rf Surface Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been understood that such extremely low R S , as observed from high-quality MgB 2 films at very low temperatures, is attributed to the s-wave nature of the order parameter in the π band [11,12]. The s-wave nature allows an exponential temperature dependence of the R S [13,14], with their R S values being lower than those of Nb films at temperatures above 4 K [15,16] 5 . Grain boundaries of MgB 2 films affect their R S only a little compared to those of YBa 2 Cu 3 O 7 (YBCO) films, with the R S of polycrystalline MgB 2 films being as low as 10 µ at 8.5 GHz at 7 K after being irradiated with 7 MeV protons [17].…”
Section: Introductionmentioning
confidence: 99%